Comprehensive assessment of paddy soil quality under land consolidation: a novel perspective of microbiology - Lin,Yaoben; Ye,Yanmei; Wu,Cifang; Yang,Jianhui; Hu,Yiming; Shi,Haokun (PeerJ, 2019)
Soil quality assessment is an important means to demonstrate how effective land consolidation is. However, the existing assessment system is not sufficient to reflect actual soil quality. So, the purpose of this study is to integrate abiological and biological indicators into a comprehensive assessment to evaluate the paddy soil quality under different land consolidation practices. Soil samples were collected from 35 paddy sites under different land consolidation practices including land merging, land leveling (LL), ditch construction (DC) and application of organic fertilizer (AO). A total of 10 paddy sites were selected under conventional tillage (CT) from non-land consolidation area as a control group in Y county, China. The results indicated that soil organic matter (OM), total nitrogen (TN), available phosphorus, bacterial functional diversity (BFD), bacterial and fungal abundances were significantly improved. Fields under LL, among all the land consolidation practices, might still face the risk of land degradation caused by low TN, OM and microbial diversity. High microbial biomass, BFD and OM were significantly higher in fields under AO in nutrient cycle. According to the results of comprehensive assessment, the samples with severe heavy metal contamination and low microbial diversity were generally concentrated in CT. These results indicated that land consolidation was an efficient technique to improve soil quality and could achieve higher quality of agricultural products.
Keywords: Land consolidation; Soil quality; Comprehensive assessment; Microbiology